Credulous on accountability at LaaRiba community: A tasawuf critical reflection - Muhammad Irfan Tarmizi; Muhammad Nur Abdullah Birton; Muhammad Muttaqin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: Accountability is a form and mechanism of responsibility that applies to all activities at the level of individuals, organizations and the social world. This study aims, first, to explore the meanings and values that underlie the collective awareness of members and administrators of the LaaRibaa Community in actualizing accountability in financial reporting; second, providing a critical reflection on the awareness and practices of accountability within the LaaRibaa community.Design/Methodology/Approach: This study applies Milles and Huberman's qualitative approach, modified with critical reflection through tasawuf concepts by Haji Abdul Malik Karim Amrullah (HAMKA). Data were collected through interviews with committees and members as well as observations on the documents. Data analysis includes the following steps: (1) data reduction, (2) data presentation, and (3) verification using the HAMKA’s tasawuf concept as an analytical tool.Research findings: The results show that the LaaRiba community's financial accountability model is influenced by many values. Al-Qur'an and hadith as fundamental values; trustworthiness and sincerity as substantial values; and please Allah (ﷻ) as the ultimate goal of managers and community members. However, this principle of trustworthiness and sincerity is practiced credulously, both from their position as public auditors and from the perspective of HAMKA's tasawuf concepts which are ihlas (sincerity) and amanah (trustworthy) (Islamic accountability).Theoretical contribution/Originity: This study found an inconsistency in the attitudes of community members or managers, on their daily occupation of being public auditors, they were very strict on the principles of accountability, but not accordingly when they act as community members or managers. This result strengthens previous findings which show a weak commitment to accountability in Islamic social institutions.Practitioner/Policy implication: To the managers of the LaaRiba community, there are three aspects that need to be fixed immediately. First, the legality of the community, so that there is legal certainty. Second, the position of the waqf contract needs to be reviewed so that it does not violate its purpose. Third, the accountability of financial reports needs to be improved in accordance with generally accepted accounting principles in Islamic social institutions